Nonlinear Bending and Snapthrough Response of Doubly Curved Laminated Shells - Aminipour, Hooman (2021)
A Master of Science thesis in Mechanical Engineering by Hooman Aminipour entitled, “Nonlinear Bending and Snapthrough Response of Doubly Curved Laminated Shells”, submitted in April 2021. Thesis advisor is Dr. Samir Emam. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).